(untitled) - Truman, Harry S. (New York, 1952)
Personal diaries, private letters, papers, and revealing interviews of Harry S. Truman, thirty-second President of the United States of America.
Keywords: Tổng thống,Presidents; Nhật kí,Diaries; Hoa Kỳ,United States